Relaxation of NH(a1?, v=1) in Collisions with H(2S): An Experimental and Theoretical Study - Defazio, P.; Petrongolo, C.; McBane, G. C.; Adam, L.; Hack, W.; Akpinar, S.; Schinke, R. (Amer Chemical Soc, 2009)
Collisions of electronically and vibrationally excited NH(a(1)Delta, v = 1) with H atoms were investigated by experimental, quantum mechanical (QM) wavepacket, and quasiclassical trajectory (QCT) methods. The NH(a(1)Delta, v = 1) total loss rate constant, corresponding to the sum of the NH vibrational relaxation, N(D-2)+H-2 formation, and electronic quenching to NH(X-3 Sigma(-)), was measured at room temperature, Most of the calculations were performed within the Born-Oppenheimer approximation, neglecting electronic quenching due to Renner-Teller Coupling because QCT calculations showed that for the loss of NH(a(1)Delta, v = 1) the contribution of quenching is negligible. The QM Study included Coriolis couplings, and the QCT study counted only trajectories ending close to a vibrational quantum level of the product diatom. The collisions are dominated by long-lived intermediate complexes, and QM probabilities and cross sections thus exhibit pronounced resonances. QM and QCT cross sections and rate coefficients of the various processes are in very good agreement. The measured rate constant is (9.1 +/- 3.3) x 10(-11) cm(3) s(-1), compared with (14.4 +/- 0.5) x 10(-11) and (15.6 +/- 1.6) x 10(-11) cm(3) s(-1), as obtained from QM and QCT calculations, respectively. The reason for the theoretical overestimation is unknown.
Keywords: Potential-Energy Surface; Real Wave-Packets; N(D-2)+H-2 Reaction; Angular-Momentum; Nh2; Transitions; Atoms; H-2; Photolysis; Molecules